Burden of human scabies in sub‐Saharan African prisons: Evidence from the west region of Cameroon. (1st March 2017) - Kouotou, Emmanuel Armand; Nansseu, Jobert Richie N; Sangare, Abdoulaye; Moguieu Bogne, Léonnelle‐Lynda; Sieleunou, Isidore; Adegbidi, Hugues; Tameyi Tatsa, Joël; Moyou Somo, Roger
Abstract: Background/Objectives: There is little data on the profile and magnitude of scabies in sub‐Saharan African prisons. The present study aimed to assess the prevalence and determinants of scabies in prisons of the west region of Cameroon. Methods: We conducted a cross‐sectional study from March to August 2014, and consecutively recruited volunteer detainees of three randomly selected prisons in the West Region of Cameroon. The diagnosis was based on clinical findings after assessment by two experienced and well‐trained dermatologists. Results: We enrolled 755 prisoners, 17 (2%) of whom were women. Their mean age was 32 ± 12 years. There were 242 cases (32%) of scabies, with significantly more cases in the most crowded prison ( P < 0.0001). Men were significantly more affected than women ( P = 0.004) and the prevalence of scabies significantly decreased when the level of education increased ( P < 0.0001). In addition to a low level of education (adjusted odds ratio (aOR) 1.90; P < 0.0001), sharing clothes/bedding (aOR 2.72; P < 0.0001) and the number of detainees per cell > 10 (aOR 1.89; P = 0.002), but not age, duration of incarceration, number of baths/week and washing/week, were independent drivers of scabies occurrence. Conclusion: Almost one‐third of prisoners suffered from scabies in our prisons. A low educational level, the sharing of clothes/bedding and number of detainees/cell > 10 were independent determinants of the disease. Urgent measures must be undertaken to reduce the burden of scabies in our prisons.